Future therapies targeted towards eliminating Candida biofilms and associated infections. Issue 3 (4th March 2017) - Bandara, H.M.H.N.; Matsubara, V. H.; Samaranayake, L. P.
ABSTRACT: Introduction : Candida species are common human commensals and cause either superficial or invasive opportunistic infections. The biofilm form of candida as opposed to its suspended, planktonic form, is predominantly associated with these infections. Alternative or adjunctive therapies are urgently needed to manage Candida infections as the currently available short arsenal of antifungal drugs has been compromised due to their systemic toxicity, cross-reactivity with other drugs, and above all, by the emergence of drug-resistant Candida species due to irrational drug use. Areas covered : Combination anti- Candida therapies, antifungal lock therapy, denture cleansers, and mouth rinses have all been proposed as alternatives for disrupting candidal biofilms on different substrates. Other suggested approaches for the management of candidiasis include the use of natural compounds, such as probiotics, plants extracts and oils, antifungal quorum sensing molecules, anti- Candida antibodies and vaccines, cytokine therapy, transfer of primed immune cells, photodynamic therapy, and nanoparticles. Expert commentary : The sparsity of currently available antifungals and the plethora of proposed anti-candidal therapies is a distinct indication of the urgent necessity to develop efficacious therapies for candidal infections. Alternative drug delivery approaches, such as probiotics, reviewed here is likely to be a reality in clinical settings in the not too distant future.